2020
DOI: 10.1111/jocn.15222
|View full text |Cite
|
Sign up to set email alerts
|

Access and referral to palliative care for patients with chronic heart failure: A qualitative study of healthcare professionals

Abstract: Background: Palliative care for individuals with chronic heart failure is recommended for improving patients' symptoms, function and overall quality of life. Despite this mandate, there is limited access and referral to specialist palliative care for individuals with chronic heart failure.Objectives: To explore healthcare professionals' perspectives on access to palliative care for patients with chronic heart failure, focussing on patient, provider and system factors.Methods: Cardiologists, palliative care spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…From the mid-2010s, studies began focusing on PC interventions for HF patients that have demonstrated potential effectiveness 33 . Research has recently focused on the problems of patients and families who respond negatively to PC interventions, such as the refusal to accept PC and the lack of readiness 30,34 . These problems are similar to the consequences of “refusal to prepare for death while feeling hindrance with life goals” and “continuation of life without worry about death” that emerged in this study.…”
Section: Discussionmentioning
confidence: 70%
“…From the mid-2010s, studies began focusing on PC interventions for HF patients that have demonstrated potential effectiveness 33 . Research has recently focused on the problems of patients and families who respond negatively to PC interventions, such as the refusal to accept PC and the lack of readiness 30,34 . These problems are similar to the consequences of “refusal to prepare for death while feeling hindrance with life goals” and “continuation of life without worry about death” that emerged in this study.…”
Section: Discussionmentioning
confidence: 70%
“…27 An integrated and collaborative model is favoured, with palliative care being provided alongside heart failure management by heart failure nurses, clinicians and allied health professionals trained in palliative care and working as a team, with specialist palliative care involved for more complex unmet needs, throughout the illness. 28,29 Earlier involvement of specialist palliative care in a collaborative manner has the potential to improve patients’ and carers’ quality of life, deliver care to the whole patient and carer, manage symptoms and coordinate services. 27 An increase in the number of individuals dying in their preferred place of death and subsequent lower hospitalisation costs are also likely positive outcomes of early, collaborative involvement of specialist palliative care on an as-needed basis.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study conducted in Australia, it was noted that even in countries where access to palliative care is widespread, there are very similar barriers to the institution of this care in HF, such as the clinical profile of the patient, the education needs of health professionals, patients, and families on palliative care, as well as the acceptance of this care by the patient. 19 It is perceived, many times, that the unawareness, especially of the patients, about their disease and its evolution, does not favor the opening for discussion about palliative care. 20 Among the strategies to minimize the lack of knowledge about palliative care in HF, a recent study applied weekly telehealth sessions led by palliative care nurse specialists to discuss relevant topics such as self-care, symptom management, and decision making.…”
Section: Discussionmentioning
confidence: 99%